Does Gendre Moderate the Influence of Social Media and Korean Wave on Consumptive Behavior - Yunara, Lutia; Novia, Aidil; Rozalinda, Rozalinda (Jurnal Iqtisaduna, 2025)
This study aims to analyze the influence of social media and the Korean Wave on the consumptive behavior of Generation Z in Padang City and examine the role of gender as a moderating variable. The method used is quantitative, with primary data from 392 respondents obtained through online surveys and questionnaires. The analysis technique used was Structural Equation Modeling (SEM) with SmartPLS. The results showed that social media had a significant effect on consumptive behavior, with an influence value of 0.410, while the Korean Wave influenced 0.498. Gender acts as a moderating variable, with the results weakening the influence of social media on consumptive behavior but strengthening the influence of the Korean Wave. The findings suggest that social media and Korean pop culture contribute to Generation Z’s consumption patterns, with gender as a factor that strengthens or weakens the relationship. This research provides insights for marketers in developing strategies that suit the characteristics of the younger generation.